Physiological effects of titrated oxygen via nasal high‐flow cannulae in COPD exacerbations: A randomized controlled cross‐over trial. Issue 6 (4th May 2017) - Pilcher, Janine; Eastlake, Leonie; Richards, Michael; Power, Sharon; Cripps, Terrianne; Bibby, Susan; Braithwaite, Irene; Weatherall, Mark; Beasley, Richard
ABSTRACT: Background and objective: Increased arterial carbon dioxide tension (PaCO2 ) is an important complication of acute exacerbations of COPD. The effects of nasal high‐flow cannulae (NHF) on PaCO2 in patients with COPD exacerbations, and whether this therapy should be used in this clinical situation, are less certain. We aimed to investigate the effect of NHF on PaCO2 in patients admitted to hospital with a COPD exacerbation. Methods: We performed a single‐centre randomized controlled cross‐over trial in 24 hospital inpatients with acute exacerbations of COPD receiving oxygen via standard nasal prongs (SNPs). Patients received both supplemental oxygen via NHF (35 L/min) and SNP for 30 min each, with oxygen titrated to maintain the patient's baseline oxygen saturation, measured by pulse oximetry (SpO2 ). Interventions were administered in random order with a minimum 15‐min washout between interventions. The primary outcome was difference in transcutaneous carbon dioxide tension (PtCO2 ) at 30 min adjusted for time zero. Results: The difference in PtCO2 adjusted for time zero was lower after 30 min for NHF compared with SNP (−1.4 mm Hg (95% CI: −2.2 to −0.6), P  = 0.001). There was no difference in SpO2 at 30 min (−0.02% (95% CI: −0.8 to 0.7), P  = 0.96). The reduction in respiratory rate for NHF at 30 min was not statistically significant (−2.0 breaths/min (95% CI: −4.5 to 0.4), P  = 0.099). Conclusion: Short‐term use of NHF results in a small reduction in PtCO2 compared with SNP in patients with acute exacerbations of COPD, but whether this is clinically significant is uncertain. Abstract : In patients with exacerbations of COPD, the short‐term use of nasal high‐flow cannulae at 35 L/min results in a small reduction in transcutaneous carbon dioxide tension (PtCO2 ) compared with standard nasal prongs. See DOI: 10.1111/resp.13092